Nasolabial island flap for management of post osteo-odonto-keratoprosthesis oroantral fistula - Nikhil Panse; Aditya Narsimhan; Prasad Dadhe (Wolters Kluwer Medknow Publications, 2021)
Osteo-odonto-keratoprosthesis (OOKP) is a procedure that is beneficial to patients with end-stage ocular disease, which is not amenable to corneal transplantation. It involves the harvest of tooth lamina and implantation of lamina cortex into the eye. The oroantral fistula (OAF) is one of the most disastrous complications of this procedure. The complication of an OAF during the harvest of a molar for an OOKP procedure can be prevented by applying a sound surgical technique. However, in case an OAF develops, it can be managed by a variety of options depending on the dimensions of the defect. In this report, we present the use of a nasolabial flap along with an upper sulcus flap for coverage of an OAF after undergoing an OOKP procedure. Measures to avoid this disastrous complication have also been discussed.